2013
DOI: 10.1016/j.ajpath.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacteria Drive Kupffer Cell Expansion via MAMP-Mediated ICAM-1 Induction on Sinusoidal Endothelium and Influence Preservation-Reperfusion Injury after Orthotopic Liver Transplantation

Abstract: Bacteria in the gut microbiome shed microbial-associated molecule patterns (MAMPs) into the portal venous circulation, where they augment various aspects of systemic immunity via low-level stimulation. Because the liver is immediately downstream of the intestines, we proposed that gut-derived MAMPs shape liver immunity and affect Kupffer cell (KC) phenotype. Germ-free (GF), antibiotic-treated (AVMN), and conventional (CL) mice were used to study KC development, function, and response to the significant stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 30 publications
4
62
1
1
Order By: Relevance
“…Consistent with these studies, treatment of rats with polymyxin B prior to liver transplantation reduced intestinal levels of Enterobacteriaceae; this reduction was correlated with decreased portal circulation endotoxin levels, decreased hepatic Kupffer cell tissue factor activity, and decreased posttransplant hepatonecrosis (87). Thus, after ischemia-reperfusion, MAMPs may participate in recruitment of Kupffer cells to the liver allograft, contributing to graft injury after liver transplantation (88). This may reflect exaggerated inflammatory responses elicited by microbial flora in the portal circulation that upregulate expression of gastrointestinal TLRs and responses to danger-associated molecular patterns (DAMPs) from damaged cells after surgery.…”
Section: Immunologic Consequences Of Dysbiosis Aftersupporting
confidence: 65%
“…Consistent with these studies, treatment of rats with polymyxin B prior to liver transplantation reduced intestinal levels of Enterobacteriaceae; this reduction was correlated with decreased portal circulation endotoxin levels, decreased hepatic Kupffer cell tissue factor activity, and decreased posttransplant hepatonecrosis (87). Thus, after ischemia-reperfusion, MAMPs may participate in recruitment of Kupffer cells to the liver allograft, contributing to graft injury after liver transplantation (88). This may reflect exaggerated inflammatory responses elicited by microbial flora in the portal circulation that upregulate expression of gastrointestinal TLRs and responses to danger-associated molecular patterns (DAMPs) from damaged cells after surgery.…”
Section: Immunologic Consequences Of Dysbiosis Aftersupporting
confidence: 65%
“…The influence of age on liver immunity development was demonstrated using Swiss Webster mice; a study showed that the establishment of commensal bacteria between 3 and 8 wk of age directly controlled the numbers, maturation, and functional activity of KCs. The numbers of total and mature KCs (F4/80 + MHCII + ) in 9-wk-old ABX and germ-free Swiss Webster mice were reduced to numbers similar to 3-wk-old counterparts (30). In a transgenic mouse model, Publicover et al demonstrated that KCs in 8-to 12-wk-old C57BL/6 mice facilitated lymphoid organization and immune priming and promoted successful immunity against HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Sinusoidal endothelial cells play an important role in warm IRI [85]. The effect of liver denervation on the expression of the sinusoidal endothelial cell-derived intercellular adhesion molecule-1 and P-selectin, that induce liver graft IRI through hepatic microcirculation impairment, was evaluated [86,87]. Administration of examethonium to donor rats before OLT leads to decreased intercellular adhesion molecule-1 and P-selectin messenger RNA levels of the liver graft reducing IRI risk.…”
Section: Hepatic Denervation and Transplanted Livermentioning
confidence: 99%